Capacity Building of the DKI Jakarta Provincial Government in Implementing E-Government - Nurdin Sialen (Best Journal of Administration and Management, 2024)
This research focuses on developing the capacity of the DKI Jakarta provincial government in implementing E-Government. The research uses a literature study approach which aims to understand the context, background and theoretical implications of developing the capacity of the DKI Jakarta Provincial Government in implementing e-Government by referring to existing literature. Researchers analyze and understand concepts, theories and approaches that are relevant to developing the capacity of the DKI Jakarta Provincial Government in implementing eGovernment through previous literature. The aim is to build a strong and in-depth framework for thinking about the urgency of developing this capacity. Given the enormity of the challenges of urbanization, demographic growth, and the complexity of urban management, information technology-based solutions are becoming increasingly important. E-Government, which offers technology integration in government administration, is one of the strategic initiatives that is expected to increase efficiency, transparency and quality of public services in Jakarta. However, despite its great potential, implementing e-Government is not a simple process. Developing technology architecture, designing services that are responsive to citizen needs, and managing changes within the bureaucracy all require significant capacity.